Coupling Influence on Signal Readout of a Dual-Parameter LC Resonant System. (25th May 2015) - Xiong, Jijun; Wei, Tanyong; Luo, Tao; Tan, Qiulin; Xue, Chenyang; Liu, Jun; Zhang, Wendong
Abstract : Dual-parameter inductive-capacitive (LC) resonant sensor is gradually becoming the measurement trend in complex harsh environments; however, the coupling between inductors greatly affects the readout signal, which becomes very difficult to resolve by means of simple mathematical tools. By changing the values of specific variables in a MATLAB code, the influence of coupling between coils on the readout signal is analyzed. Our preliminary conclusions underline that changing the coupling to antenna greatly affects the readout signal, but it simultaneously influences the other signal. Whenf 01 = f 02, it is better to broaden the difference between the two coupling coefficientsk 1 andk 2 . On the other side, whenf 01 is smaller thanf 02, it is better to decrease the coupling between sensor inductorsk 12, in order to obtain two readout signals averaged in strength. Finally, a test system including a discrete capacitor soldered to a printed circuit board (PCB) based planar spiral coil is built, and the readout signals under different relative inductors positions are analyzed. All experimental results are in good agreement with the results of the MATLAB simulation.